The Evolution of Research on European Medieval and Early Modern History at Ukrainian Universities - Makliuk, Olga; Cherkasov, Stanislav (Вісник гуманітарних наук, 2025)
The purpose of the research paper is to highlight the evolution of European Medieval and Early Modern history studies at Ukrainian universities within the broader framework of decolonial rethinking in the humanities. Historically, Ukrainian scholarship has been shaped by imperial and Soviet paradigms that limited academic discourse and reinforced ideological constraints. The study of Europe’s Medieval and Early Modern periods has played a crucial role in forming the academic culture of Ukrainian higher education, shaping political legitimacy, cultural norms, and identity narratives. Given the ongoing full-scale war in Ukraine, questions of historical legacy, cultural autonomy, and identity have gained heightened public and political significance, adding urgency to reexamining this field. The scientific novelty lies in the exploration of different perspectives and versions in an attempt to reexamine academic traditions surrounding the study of Medieval and Early Modern European history at leading Ukrainian universities, including Taras Shevchenko National University of Kyiv, Ivan Franko National University of Lviv, V. N. Karazin Kharkiv National University, I. I. Mechnikov Odesa National University, and Yuriy Fedkovych Chernivtsi National University. These institutions were selected for their historical continuity, existence of specialized history departments, academic presence through dissertations and publications, and regional diversity, allowing for an examination of varied intellectual traditions across Ukraine. The study of European Medieval and Early Modern history at Ukrainian universities has undergone a dynamic transformation, reflecting broader political, intellectual, and institutional shifts over time. From its early stages under imperial and Soviet influences – when research was often constrained by ideological frameworks – to the post-independence era marked by academic renewal and increasing international integration, the field has progressively embraced methodological pluralism and interdisciplinary collaboration. In recent decades, Ukrainian scholars have expanded their thematic focus, adopted new theoretical approaches, and contributed more actively to global historiographical debates. Despite ongoing challenges, including limited funding and the consequences of war, the resilience and adaptability of Ukrainian historical scholarship offer strong potential for further development. Strengthening academic networks, enhancing digital and archival access, and fostering multilingual competencies will be key to ensuring the continued evolution and global relevance of Medieval and Early Modern studies in Ukraine. Despite the availability of dissertations and academic articles, the evolution of this research field remains underexplored and unsystematized. Institutional studies focusing on academic lineages and thematic developments are largely absent. Since Ukraine’s independence in the 1990s, there has been a significant shift toward Western academic paradigms, diversification of research topics, and critical reassessment of imperial legacies. Collaborative international programs have further supported this transformation, fostering a more pluralistic and reflective scholarly environment. By reconstructing the academic history and current state of Medieval and Early Modern European history research in Ukraine, this article contributes to understanding the regional specificities, intellectual influences, and the potential for decolonial rethinking of historical knowledge in Ukrainian academia.